2021
DOI: 10.3390/foods10112594
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Content of Street Food and Takeaway Food Purchased in Urban Bosnia and Herzegovina

Abstract: Street food (SF) and takeaway food (TAF) are important sources of out-of-home meals in urban Bosnia and Herzegovina, where diet-related non-communicable diseases are growing rapidly. This study aimed to characterise SF and TAF purchased in urban areas of Bosnia and Herzegovina, regarding customers’ characteristics and the nutritional composition of the foods and beverages. A cross-sectional study was conducted in Sarajevo and Banja Luka in 2017. SF (n = 194) and TAF vending sites (n = 154) were selected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…This study found that the gas chromatography did not detect TFAs in any of the local street foods, which is not in agreement with the findings from other countries in the Asian [ 5 , 6 , 8 , 12 ], European [ 7 , 9 , 37 ], and African [ 10 ] regions. This is possibly due to varying ingredients used in the local street foods in other countries.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…This study found that the gas chromatography did not detect TFAs in any of the local street foods, which is not in agreement with the findings from other countries in the Asian [ 5 , 6 , 8 , 12 ], European [ 7 , 9 , 37 ], and African [ 10 ] regions. This is possibly due to varying ingredients used in the local street foods in other countries.…”
Section: Discussioncontrasting
confidence: 94%
“…Fats in food exist in varying proportions of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs) and trans fatty acids (TFAs) [ 4 ]. Several studies from other countries (Eastern Europe, Central Asia, Southeast Asia and Africa) found the presence of TFAs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and high amounts of SFAs [ 6 , 7 , 8 ] in their local street food.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each customer, two observers independently registered the food items purchased and respective quantities. Inter-observer concordance was evaluated using Cohen’s kappa (K) with 95% confidence interval (95%CI), being high to very high, regarding both variables (food item purchased: 98.2% agreement, K = 0.98, 95%CI 0.97–1.00; quantity purchased: 92.0% agreement, K = 0.89, 95%CI 0.86–0.92) [ 23 ]. Disagreements between observers were solved using a set of standardized criteria: (1) if the two observers registered different food items, the conflicting items were checked for their availability on the corresponding vending site (if only one of the conflicting items was available, that was the observation assumed, and both observations were disregarded if the conflicting items were both available or not available); (2) if the two observers registered the same food item, but with different degrees of specificity, the broadest observation was assumed; (3) if the two observers registered a different number of food items for the same customer, the observation with the larger number of food items available was assumed; and (4) if two observers registered the same food item, but different quantities, the average quantity of the two observations was assumed.…”
Section: Methodsmentioning
confidence: 99%